EFEK INHALASI MINYAK KAYU PUTIH (Melaleuca leucadendron) TERHADAP JUMLAH SEL SPERMATID MENCIT JANTAN (Mus musculus) YANG DIINDUKSI STRES AKUT - Aldy M Wajabula; Merlin M Maelissa; Halidah Rahawarin (Fakultas Kedokteran Universitas Pattimura, 2022)
Stress refers to events that can affect a person's physical and psychological condition, including in the process of spermatogenesis. Eucalyptus oil has an antidepressant effect which acts to prevent the stress from continuing. This study aims to determine how the administration of eucalyptus oil inhalation on the number of spermatid cells in male mice (Mus musculus) exposed to acute stress. This research is a true experimental study with a posttest only control group design approach. A total of 28 adult male mice selected by simple random sampling were grouped into four groups, namely the normal control group (no treatment); negative control group (given exposure to acute stress); positive control group (administered 0.2 mL alprazolam and exposure to acute stress); treatment group (given 0.5 mL of eucalyptus oil and exposure to acute stress). Stress treatment was carried out for six minutes per day in 14 days. The results of the study using the oneway ANOVA statistical test showed that there was a difference between each experimental group (p<0.001). Tukey's further test results showed that there was a significant difference between the eucalyptus oil group given stress exposure with intervention and the negative control group given stress exposure without intervention (p<0.001). This proves that eucalyptus oil has a preventive effect on stress and prevents a decrease in the number of spermatid cells.